The Effect of Tapak Dara (Catharanthus roseus) Leaf Extract on The Growth of Mice (Mus Musculus) Ovarian Follicles - Mawaddah Fatin Nuradiah; I Wayan Merta Merta; Kusmiyati Kusmiyati (Jurnal Biologi Tropis, 2023)
Tapak dara (Catharanthus roseus) leaf contain phytoestrogen compounds such as flavonoids, isoflavonoids, saponins, and tannins, and contain alkaloid compounds. Phytoestrogens are compounds contained in plants, having a chemical structure resembling 17β-Estradiol in the body's natural estrogen. This study aims to determine the effect of tapak dara leaf extract on the growth of ovarian follicles of mice (Mus musculus), consisting of primary follicles, secondary, tertiary, and de Graaf follicles. This research method is true experiment and Posstest-Only Control with a quantitative approach. Sampling was carried out randomized block design (RBD). The growth of mice ovarian follicles is known by counting the number of mice ovarian follicles, analyzed using the ANOVA one-way test analysis method at a sig. level of 5% (α = 0.05), then if there is a difference, proceed with a further test of Least Significant Difference) at a sig. level of 5% (α = 0.05). Data analysis using Microsoft Excel 2010. The results of the hypothesis test using One Way ANOVA stated that Fcalculate > Ftable at sum of primary follicles, which means that there is a real difference and Ha is accepted. The results of hypothesis tests at sum of secondary, tertiary, and de Graaf follicles stated that Fcalculate < Ftable, which means there is no real difference and Ha is rejected. The conclusion of this study is that tapak dara leaf extract has a significant effect on the growth of primary follicles, but does not significantly affect the growth of secondary, tertiary, and de Graaf follicles.